2020
DOI: 10.7717/peerj.9581
|View full text |Cite
|
Sign up to set email alerts
|

Identification of olfactory genes of a forensically important blow fly, Aldrichina grahami (Diptera: Calliphoridae)

Abstract: Background The time-length between the first colonization of necrophagous insect on the corpse and the beginning of investigation represents the most important forensic concept of minimum post-mortem inference (PMImin). Before colonization, the time spent by an insect to detect and locate a corpse could significantly influence the PMImin estimation. The olfactory system plays an important role in insect food foraging behavior. Proteins like odorant binding proteins (OBPs), chemosensory proteins (CSPs), odorant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 97 publications
1
11
1
Order By: Relevance
“…The ability of an insect to recognise odours relies heavily on their OBPs ( Barbosa et al, 2018 ), as these small, water-soluble proteins facilitate the transport of odour molecules through the sensory lymph and serve as connections between external environmental stimuli and odour receptors ( Pelosi et al, 2006 ; Leal, 2013 ; Han et al, 2020 ). In this study, 35 candidate OBPs were identified in the antennal transcriptome of B. cucurbitae .…”
Section: Discussionmentioning
confidence: 99%
“…The ability of an insect to recognise odours relies heavily on their OBPs ( Barbosa et al, 2018 ), as these small, water-soluble proteins facilitate the transport of odour molecules through the sensory lymph and serve as connections between external environmental stimuli and odour receptors ( Pelosi et al, 2006 ; Leal, 2013 ; Han et al, 2020 ). In this study, 35 candidate OBPs were identified in the antennal transcriptome of B. cucurbitae .…”
Section: Discussionmentioning
confidence: 99%
“…The ability of an insect to recognize odours relies heavily on their OBPs (Barbosa et al, 2018), as these small, water-soluble proteins facilitate the transport of odour molecules through the sensory lymph and serve as connections between external environmental stimuli and odour receptors (Han et al, 2020;Leal, 2013;Pelosi et al, 2006)…”
Section: Discussionmentioning
confidence: 99%
“…2). Information including the unigene reference, length, and best Blastx hit for all 35 OBPs is listed in Table 1.…”
Section: Characterization Of Odorant Binding Proteinsmentioning
confidence: 99%
“…Finding suitable hosts for oviposition is primarily guided by olfactory stimuli [ 16 , 19 ]. Once a host is selected, females use receptors associated with the labellum, tarsi and ovipositor to select an oviposition site which will provide the larvae with enough food to complete their development [ 23 25 ]. In blowflies (as in other insects), chemical compounds from the surrounding environment enter the fly's body through porous sensilla located in the cuticle [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Different sensory receptors have been identified in blowflies, namely, membrane receptors such as odorant receptors (ORs), gustatory receptors (GRs) and ionotropic receptors (IRs) [ 25 , 27 29 ], and odor-molecule carriers, including chemosensory proteins (CSPs), odorant-binding proteins (OBPs) and CD36-sensory neuron membrane proteins (CD36/SNMPs) [ 25 , 27 30 ]. However, beyond these descriptive works, there is no functional information on these receptors in Calliphoridae.…”
Section: Introductionmentioning
confidence: 99%